2021
DOI: 10.3389/fgene.2021.665769
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Associations of BMI and Fatty Acids With DNA Methylation in Fasting and Postprandial States in Men

Abstract: We have previously shown that blood global DNA methylation (DNAm) differs between postprandial state (PS) and fasting state (FS) and is associated with BMI and polyunsaturated fatty acid (PUFA) (negatively and positively, respectively) in 12 metabolically healthy adult Mexican men (AMM cohort) equally distributed among conventional BMI classes. Here, we detailed those associations at CpG dinucleotide level by exploiting the Infinium methylation EPIC array (Illumina). We sought differentially methylated CpG (dm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
4
1
Order By: Relevance
“…Despite this, we suggest that future studies be conducted with an experimental design that makes it possible to investigate the influence of duration and energy demand on MRF epigenetic regulation. Also, some of the aforementioned differences between our data and previous results could be explained by the control standard meal we provided in our experimental design to avoid possible fasting effects on DNA methylation and mRNA expression (24–26). Moreover, we acknowledge that we only analyzed DNA methylation in one specific region of each target gene, raising the possibility that other regions within the genes may have different sensitivities to exercise than those reported in the current investigation.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Despite this, we suggest that future studies be conducted with an experimental design that makes it possible to investigate the influence of duration and energy demand on MRF epigenetic regulation. Also, some of the aforementioned differences between our data and previous results could be explained by the control standard meal we provided in our experimental design to avoid possible fasting effects on DNA methylation and mRNA expression (24–26). Moreover, we acknowledge that we only analyzed DNA methylation in one specific region of each target gene, raising the possibility that other regions within the genes may have different sensitivities to exercise than those reported in the current investigation.…”
Section: Discussioncontrasting
confidence: 76%
“…On the evening before an experimental testing session, a standard meal (3 g of carbohydrate, 0.5 g of protein, and 0.3 g of fat per kilogram of body mass [23]) was provided to the participants as the last meal of the day. Three hours before each muscle biopsy, participants were provided a small meal (60 g of CHO, 10 g of proteins, and 23.8 g of fat, total energy 2001 kJ) to avoid possible fasting effects on DNA methylation and mRNA expression (24)(25)(26).…”
Section: Diet and Exercise Controlmentioning
confidence: 99%
“…An excess of palmitic and other FAs impacts DNA methylation, therefore leading to epigenetic alteration, as observed within different cell types [ 56 ], and in fasting to post-prandial transitions in obese humans [ 57 , 58 ]. These events are conceptually similar to the dynamic reprogramming during embryonic development, by which environmental stimuli (including assisted reproductive technologies) lead to acquisition of a stable, modified genotype later in life [ 59 ] and, in this case, loss of pregnancy competence.…”
Section: Discussionmentioning
confidence: 99%
“…We found palmitic and stearic acid to be the most correlated more often with DNA methylation of the CpGs linked with SFA. Earlier studies in humans and humanderived cells have found that both palmitic and stearic acids actively interact with the epigenome [25,27,29,60]. For instance, excess palmitic and stearic acid is known to induce inflammation and metabolic dysregulations in various cell models (including primary murine hepatocytes) along with alterations in histone acetylation and DNA methylation [61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%